(untitled) (قضايا سياسية, 2025)
The availability of law is linked to the presence of society - any society - as well as the link between authority and it, because authority is the one that enacts laws through its parliamentary councils, especially under democratic political systems. If the law is necessary for the lives of individuals and for organizing social life, it constitutes a restriction on them; because the freedom of the individual occupies a fundamental pillar in democratic life. From here arises the conflict between law and freedom, that is, the conflict arises between law and democracy. So how does the idea of ​​law reconcile with the idea of ​​democracy?